2019
DOI: 10.34087/cbusbed.548466
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelerin Psikososyal Sorunlarının ve Stresle Başa Çıkma Tarzlarının İncelenmesi

Abstract: Öz Amaç: Bu çalışma hemşirelerin psikososyal sorunlarının ve stresle başa çıkma tarzlarının belirlenmesi amacıyla yapıldı. Gereç ve Yöntem: Tanımlayıcı tipte planlanan çalışma, Nisan 2018 -Haziran 2018 tarihleri arasında Menemen Devlet Hastanesinde yürütüldü. Çalışmanın örneklemini bu hastanede görev yapan toplam 184 hemşire oluşturdu. Verilerin toplanmasında, Kişisel Bilgi formu, Hastane Anksiyete Depresyon Ölçeği (HAD) ve Stresle Başa Çıkma Tarzları Ölçeği kullanıldı. Verilerin analizinde sayı yüzde, Mann Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
1
0
1
Order By: Relevance
“…Maytum et al (2004), in their study on nurses working with children with chronic diseases, suggested a significant relationship between compassion fatigue and burnout. Similar empirical findings are also found in other studies on nurses in the literature (Adanir, 2019). Although not on nurses, studies on health workers (Weintraub et al, 2016) and hospice workers (Slocum-Gori et al, 2011) also found a positive relationship between compassion fatigue and burnout.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Maytum et al (2004), in their study on nurses working with children with chronic diseases, suggested a significant relationship between compassion fatigue and burnout. Similar empirical findings are also found in other studies on nurses in the literature (Adanir, 2019). Although not on nurses, studies on health workers (Weintraub et al, 2016) and hospice workers (Slocum-Gori et al, 2011) also found a positive relationship between compassion fatigue and burnout.…”
Section: Discussionsupporting
confidence: 91%
“…Similar and different results are found in the literature. Firstly, compassion fatigue, which was detected at low levels in some studies (Chen et al, 2018), was found at moderate levels in some studies (Özdelikara and Babur, 2020) and high levels in others (Adanir, 2019). It is possible to express the reasons for these differences as the health system and date range of the researches.…”
Section: Discussionmentioning
confidence: 99%
“…(2018)'nın Yunanistan'da psikiyatri kliniklerinde çalışan hemşirelerle gerçekleştirdikleri çalışmada, hemşirelerin en fazla problem çözme, pozitif değerlendirme, sosyal destek arama gibi etkili başa çıkma yöntemlerini kullandıkları belirtilmektedir (25). Psikiyatri dışındaki kliniklerde çalışan hemşirelerin başa çıkma tarzlarının değerlendirildiği çalışmalarda da hemşirelerin en fazla kendine güvenli yaklaşım, iyimser yaklaşım ve sosyal destek aramayı kullandıkları bildirilmiştir (26)(27)(28). Bu çalışmanın bu sonucu var olan literatürle benzerdir.…”
Section: Discussionunclassified